PERSONAL HISTORY CORRELATES OF PERFORMANCE AMONG MILITARY PERSONNEL IN SMALL ANTARCTIC STATIONS - Nelson, Paul D.; Gunderson, E. K. (1963)
Personal history data were evaluated in relation to performance criterion measures for sixty-four Navy personnel each of whom had spent one year at an Antarctic scientific station. The four criteria included an evaluation of the man's social compatibility, emotional composure, and task efforts. As in previous studies of Antarctic station personnel, age was significantly related to performance. In the present study it was particularly related, in a positive direction, to emotional composure. Associated with age, but not significantly related to the criteria as individual items, were years of experience, previous stressful duty assignments, and advancement in rate. A second set of results centered about the concept of personal activities of an avocational nature. Individuals who were relatively heavy readers, had several hobbies, were active in sports, and belonged to various clubs were considered to be active individuals. Such activity, particularly for self oriented activity such as reading and hobbies, was negatively related to social compatibility. The third major find was that individuals with a past history of delinquent behavior tended to perform less well than those without such a history.